Taboo Words in Movie Sequels 21 and 22 Jump Street - Dianty Saraswati Giri, Ni Luh; Budiasa, I Gede (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p27, 2018)
The current study entitled “Taboo Words in Movie Sequels 21 and 22 Jump Street” aims to identify the types, functions and the dominant type of taboo words uttered by the characters in the movies 21 and 22 Jump Street.The data in this study were chosen from the conversations among the characters in the movies, and were collected through documentation method. This study applied qualitative method for analyzing the types and functions of taboo words in the movies. In addition, this study also used quantitative method to see the dominant types of taboo words in the movie, in a form of percentage. The results of the analysis are stated as follows. Firstly, four types of taboo words occur in the characters’ utterances in the movies 21 and 22 Jump Street. They are obscenity, profanity, vulgarity and epithet. Secondly, four functions of taboo words were also found in the movies namely to show contempt, to draw attention to oneself, to be provocative, and to mock authority. The dominant type of taboo words in both movies is Obscenity type.